2014
DOI: 10.1590/1516-1439.312114
|View full text |Cite
|
Sign up to set email alerts
|

The Role of cobalt and nickel intermetallic phases on the mechanical properties and microstructure evolution of Al-Zn-Mg-Cu alloys

Abstract: In this study, the effects of cobalt and nickel additions on microstructure evolution and mechanical properties of Al-Zn-Mg-Cu alloys produced by chill casting process were investigated. Al-Zn-MgCu aluminum alloys containing Ni and Co additives were homogenized at different heat treatment conditions, aged at 120°C for 24 h, and retrogressed at 180°C for 30 min then re-aged at 120°C for 24h.Comparison of the ultimate tensile strength of the Al-Zn-Mg-Cu base alloy underwent RRA temper process with that of the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
1
Order By: Relevance
“…These intermetallics may have nucleated on some of the TiB 2 particles, thus rendering them inactive for nucleation of a-Al. However, this result is contradictory to the findings by Naeem et al 12 who found that grain refinement occurred on addition of Co and Ni to an Al-Zn-Mg-Cu alloy.…”
Section: Resultscontrasting
confidence: 99%
“…These intermetallics may have nucleated on some of the TiB 2 particles, thus rendering them inactive for nucleation of a-Al. However, this result is contradictory to the findings by Naeem et al 12 who found that grain refinement occurred on addition of Co and Ni to an Al-Zn-Mg-Cu alloy.…”
Section: Resultscontrasting
confidence: 99%
“…The mechanical properties and application the both automotive and aircraft parts of Al-alloys are dependent of added elements [1,3]. Metallic and non-metallic elements such as Fe, Cu, Pb, In, Zn, Ni, Mg, Si, Ti, Sn, etc; are responsible to improve the mechanical properties when commercial alloys Al-based are investigated [2,[4][5][6][7]. When Zn content is utilized, a liquid phase formation in an Al-Cu binary system is formed [8].…”
Section: Introductionmentioning
confidence: 99%